Strategic Imperatives of Muslim Leadership in Post-War Sri Lanka: Citizenship, Rights and Reconciliation (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This study examines how a few selected mainstream Sri Lankan Muslim civil organisations have been responding to the Sinhala Buddhist ideological paradigm in post-war Sri Lanka. The ideology perceives that Sinhala Buddhists are true citizens of Sri Lanka while minorities are “others” or “guests”. Hence, the ideology plays a structural role in generating anti-Muslim sentiments in post-war Sri Lanka. Contrary to prevailing wisdom which argues that minorities attempt to deconstruct the majoritarian ideological foundation in their struggle for equality, dominant and mainstream Muslim civil society organisations in Sri Lanka have chosen to reconcile with it while resisting only its practical implications upon the community. Even though this strategy brings self-contradictory elements into play on theoretical grounds, Muslim civil society organisations think that it is a practically reasonable strategy given the developing socio-political context of the state. Based on primary and secondary data and the thematic qualitative analysis, this study builds an argument by analysing discourses of the selected mainstream Muslim organisations that minorities pick strategies for their struggle against majoritarian state and ideology taking their political and other demographical realities into account. Hence, their choices are not static but rather dynamic.